Sanskrit Astronomical Tables - Montelle, Clemency (Sources and Studies in the History of Mathematics and Physical Sciences,, 2018)
This groundbreaking volume provides an up-to-date, accessible guide to Sanskrit astronomical tables and their analysis. It begins with an overview of Indian mathematical astronomy and its literature, including table texts, in the context of history of pre-modern astronomy. It then discusses the primary mathematical astronomy content of table texts and the attempted taxonomy of this genre before diving into the broad outlines of their representation in the Sanskrit scientific manuscript corpus. Finally, the authors survey the major categories of individual tables compiled in these texts, complete with brief analyses of some of the methods for constructing and using them, and then chronicle the evolution of the table-text genre and the impacts of its changing role on the discipline of Sanskrit jyotiṣa. There are also three appendices: one inventories all the identified individual works in the genre currently known to the authors; one provides reference information about the details of all the notational, calendric, astronomical, and other classification systems invoked in the study; and one serves as a glossary of the relevant Sanskrit terms.